Indigenous graphic communication systems : a theoretical approach - Offner, Jerome A.; Mikulska, Katarzyna (University Press of Colorado, 2019)
"Challenges Western academic views on what writing is and explores how these concepts can be improved by analyzing the sophisticated graphic communication systems found in Central Mesoamerica and Andean South America. Exploring and rejecting the Western notion that writing exists only to record the chain of speech"--Provided by publisher